2007
DOI: 10.1902/jop.2007.060349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet‐Rich Plasma on the Healing of Intrabony Defects Treated With an Anorganic Bovine Bone Mineral and Expanded Polytetrafluoroethylene Membranes

Abstract: Within its limits, the present study has shown that, at 1 year after regenerative therapy in periodontal intrabony defects, optimal clinical results were obtained with ABBM + GTR with a non-resorbable barrier, with or without the addition of PRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 36 publications
6
85
0
1
Order By: Relevance
“…But when the local conditions are not optimum, PRP gels alone are not strong enough to promote a clinical filling equivalent to the dense bone filling reached with a bone substitute [50]. Most of the randomized controlled clinical trials(RCTs) demonstrated that the addition of PRP to certain regenerative materials, doi: 10.7243/2050-1218-2-11 namely bioactive glass [51], b-TCP [52], BM and e-PTFE membranes [53], b-TCP and e-PTFE membranes [54], BM and collagen membranes [23] and BM and EMD [55], failed to confer statistically significant additive benefits in the therapy of periodontal intraosseous defects. However, according to other RCTs such adjunctive positive outcomes may result from other combinations of PRP, namely together with BM [28], DFDBA [56] and hydroxyapatite [22].…”
Section: Discussionmentioning
confidence: 99%
“…But when the local conditions are not optimum, PRP gels alone are not strong enough to promote a clinical filling equivalent to the dense bone filling reached with a bone substitute [50]. Most of the randomized controlled clinical trials(RCTs) demonstrated that the addition of PRP to certain regenerative materials, doi: 10.7243/2050-1218-2-11 namely bioactive glass [51], b-TCP [52], BM and e-PTFE membranes [53], b-TCP and e-PTFE membranes [54], BM and collagen membranes [23] and BM and EMD [55], failed to confer statistically significant additive benefits in the therapy of periodontal intraosseous defects. However, according to other RCTs such adjunctive positive outcomes may result from other combinations of PRP, namely together with BM [28], DFDBA [56] and hydroxyapatite [22].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on the efficacy of alloplastic bone grafts, mainly HA combined with PRP, allografts like demineralized bone, barriers for guided tissue regeneration either alone or in combination with above mentioned graft materials on bone and periodontal healing [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic periodontal disease displaying one intra-bony defect, PRP combined with an organic bovine bone mineral application did not show a difference in parameters like bleeding on probing, probing depth, gingival recession and clinical attachment level compared to an organic bovine bone mineral application alone [28]. Dodson [26] studied efficacy of grafting third molar extraction sites with demineralized bone powder on periodontal healing.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gottlow et al (50) took block sections of 12 hopeless teeth treated with ePTFE membranes and found new bone growth to be an average of 5.1 mm and an average clinical attachment level (CAL) gain of 5.6 mm. Recent studies showed that intrabony defects treated with ePTFE membranes can be expected to undergo between 3.0-5.0 mm of bone fill with 4.0-7.0 mm CAL gain, regardless of whether a bone replacement graft is placed concomitantly (51)(52)(53)(54). One study compared the use of ePTFE membranes versus no membranes in the treatment of periapical lesions after apical surgery (55).…”
Section: Nonresorbable Membranesmentioning
confidence: 99%